Acibenzolar-S-methyl in control of rust and coffee plant cercosporiose in field conditions - Monteiro Fernandes, Luiz Henrique; Vilela de Resende, Mário Lúcio; Borges Pereira, Ricardo; Garcia Costa, Bruno Henrique; Andrade Monteiro, Ana Cristina; Ribeiro Júnior, Pedro Martins (Coffee Science - ISSN 1984-3909, 2013)
The objective of this study was to evaluate the effect of inducing resistance acibenzolar-S-methyl (ASM), associated or not with the fungicide azoxystrobin + cyproconazole base, the control of Cercospora leaf rust and coffee under field conditions. The test was conducted in two crop years (2007/2008 and 2008/2009), in commercial plantation with cultivar Mundo Novo. The treatments were: ASM (25 g ha-1) applied 5 times monthly (December-Aprilharvest each year); fungicide (500 mL ha-1) and fungicide mixture (500 mL ha-1) + ASM applied 3 times (December,February and April of each crop year), the fungicide mixture (500 mL ha-1) applied 3 times (December, February and April of each crop year) + ASM applied 5 times (December to April of each crop year) , the fungicide mixture (750mL ha-1) applied 2 times (December and March of each crop year) + ASM applied 5 times (December to April of each crop year) and untreated. The rust control (84%) provided by the ASM was statistically similar to the treatment withthe fungicide (94%) in low crop year (2008/2009), when the intensity of the disease was not as high as in the year of crop high (2007/2008). In high crop year, ASM not controlled the cercospora, whereas in low crop years controlled the cercosporiose this product (77%) of the fungicide lower form (92%) and their mixtures (89-94%). In low harvest year, the ASM can be used to control Cercospora leaf rust and coffee and compatibility presented with the fungicide azoxystrobin + cyproconazole.